- #1

Gonzolo

## Main Question or Discussion Point

Hi, I want fit the following equation to a set of data points :

[tex]y = A(exp(-Bx)-exp(-Cx)))[/tex]

I found how to determine A and B for one exp : y = Aexp(-Bx), but I'm not sure if there's a formula for A, B and C in such a sum (or difference) of exponentials. Thanks.

[tex]y = A(exp(-Bx)-exp(-Cx)))[/tex]

I found how to determine A and B for one exp : y = Aexp(-Bx), but I'm not sure if there's a formula for A, B and C in such a sum (or difference) of exponentials. Thanks.